Use of Flavonoids and Cinnamates, the Main Photoprotectors with Natural Origin - Alesandra R. Nunes; Ícaro G. P. Vieira; Dinalva B. Queiroz; Antonio Linkoln Alves Borges Leal; Selene Maia Morais; Débora Feitosa Muniz; João Tavares Calixto-Junior; Henrique Douglas Melo Coutinho (Advances in Pharmacological Sciences)
Many pathological problems are initiated by ultraviolet radiation (UVR), such as skin cancer, the most commonly diagnosed cancer worldwide. The UVA (320–400 nm) and UVB (290–320 nm) wavelengths may cause effects such as photoaging, DNA damage, and a series of cellular alterations. The UVA radiation can damage the DNA, oxidize the lipids, and produce dangerous free radicals, which can cause inflammation, modify the gene expression in response to stress, and weaken the skin immune response. With a minor penetration, the UVB radiation is more harmful, being responsible for immediate damage. Ultraviolet radiation light emitted by the sun is considered necessary for the existence of life but cause radiation problems, especially in the skin. The photoprotective activities of plant extracts and isolated composts were evaluated by many reports, as well as the correlation of these compounds with the antioxidant activity. This review presents plant compounds with interest to the cosmetic industry to be used in sunscreens such as flavonoids and cinnamates.